The Implementation of a Web-Based Outdoor Equipment Rental System Design (Case Study: L3 Adventure) - Dulkarnain, As’ad; Eviyanti, Ade (International Journal on Human-Computing Studies, 2025)
The advancement of information technology has transformed work methods and data management, especially among Gen Z. UMKM L3 Adventure, which rents out camping equipment, still uses manual processes for booking and data management. The COVID-19 pandemic highlighted the need for adopting an online booking system to reduce physical contact and enhance operational efficiency. This research aims to develop a web-based information system for L3 Adventure, focusing on designing an efficient and accessible online camping equipment booking system. A qualitative and quantitative approach was used, with structured surveys conducted at L3 Adventure in Sukodono, Sidoarjo. Data was collected through observation, interviews, and relevant literature. The research findings indicate that the web-based system improves data management and booking efficiency. The system employs a waterfall design model and was tested using the blackbox method to ensure its functionality. This study contributes to the development of outdoor equipment rental information systems, aiming to enhance efficiency and user experience at L3 Adventure.